COGNITIVE AND SOCIOCULTURAL FACTORS IN LANGUAGE ACQUISITION: AN INTERACTIONAL PERSPECTIVE - Umaraliyeva, Munojat Mashrabovna; Bozorboyeva , Omina Aliyevna (Educational Research in Universal Sciences, 2023)
This article focuses on the influence of cognitive and sociocultural factors in the process of learning a second or foreign language. Moreover, the interaction between the cognitive and sociocultural factors is mentioned and explained with relevant examples.